KESIAPAN TAMAN KANAK-KANAK DALAM PENYELENGGARAAN KELAS INKLUSI DILIHAT PROGRAM KEGIATAN PEMBELAJARAN - Mastuti, Devi (BELIA: Early Childhood Education Papers, 2014)
Education for all began intensively conducted by the Indonesian government, one of them through inclusive education . Inclusive education needs to take place from pre- school level, it is that children with special needs receive appropriate care from an early age. Based on observations in the field, there are several kindergartens who have children with special needs in the classroom. Providing education inclusion criteria, one of which is a program of learning activities. This makes researchers interested in carrying out research on learning activity programs in kindergarten who have children with special needs in the classroom. This study aims to determine the extent of readiness of preschool inclusion class in organizing visits of program learning activities. This type of research is descriptive qualitative. Research informants were teachers, principals and parents kindergarten class organizers Gajahmungkur inclusion in the District of Semarang. Methods of data collection through interview,observation and documentation. The validity of research data using triangulation. Data analysis using data reduction, data display and data verification. Results showed that planning activities in the classroom with special needs children who are still at the planning of learning activities for regular kindergarten. The existence of children with special needs in the classroom becomes a special concern for teachers, but does not necessarily change the curriculum applied in the institution. Implementation of learning activities that occur in kindergarten inclusion class organizers conducted by classroom teachers to deliver innovations that are expected to stimulate children with special needs. Indirectly provide service teachers to encourage children to do activities such asfriends, but limited capabilities that can be done with special needs.